2020
DOI: 10.4028/www.scientific.net/ssp.304.75
|View full text |Cite
|
Sign up to set email alerts
|

Comparative of the Use of Carbon and Steel Fiber to the Mechanical Properties of Self Compacting Concrete

Abstract: This research is a comparative study, the use of carbon fiber and steel fiber for Self-Compacting Concrete (SCC). In previous studies, it was proven that the addition of steel fibers can increase the compressive and tensile strength of SCC. While carbon fiber is one of the most widely used materials for structural reinforcement in recent years. Therefore it is necessary to do a comparative study of the use of carbon fiber if applied to SCC. The percentage increase in carbon fiber and steel is 0.5%, 1%, and 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…After reaching the peak stress, it entered the stage of crack instability and propagation, and the crack developed rapidly, and the splitting sound in the specimen became more obvious, which indicated that steel fiber played a more significant role in cracking resistance. In the descending section of the curve, the slope was negative; it first reached an inflection point, then reached the point of maximum curvature, and finally, the curve slowly descended, tended to be flat, and entered the stage of residual strength [23]. The workability and workability of the fresh concrete mixture did not changed obviously, and the mixing of steel fiber did not change the mixture ratio of raw materials.…”
Section: Discussionmentioning
confidence: 95%
“…After reaching the peak stress, it entered the stage of crack instability and propagation, and the crack developed rapidly, and the splitting sound in the specimen became more obvious, which indicated that steel fiber played a more significant role in cracking resistance. In the descending section of the curve, the slope was negative; it first reached an inflection point, then reached the point of maximum curvature, and finally, the curve slowly descended, tended to be flat, and entered the stage of residual strength [23]. The workability and workability of the fresh concrete mixture did not changed obviously, and the mixing of steel fiber did not change the mixture ratio of raw materials.…”
Section: Discussionmentioning
confidence: 95%